2015
DOI: 10.1177/0748730415621412
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Recording of Circadian Per1 and Per2 Expression in the Suprachiasmatic Nucleus of Freely Moving Rats

Abstract: Measuring real-time gene activity in the brains of freely moving animals presents a challenging issue in neuroscience research. Circadian gene expression in neurons of the suprachiasmatic nucleus (SCN), a small nucleus in the hypothalamus, is reflected in behavioral rhythmicity. Cellular oscillatory gene expression is generated by a transcription-translation feedback loop of clock genes including 2 oscillatory genes, Per1 and Per2. Here we have succeeded in real-time monitoring of Per1 and Per2 transcription s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…In mammals, the expression of core clock genes has been confirmed not only in the SCN but also in other brain structures, including the cortex and HC (Namihira et al, 1999 ; Reick et al, 2001 ; Shieh, 2003 ; Jilg et al, 2010 ; Ono et al, 2015 ; Riddle et al, 2016 ; Yamaguchi et al, 2016 ). Moreover, several studies have shown that clock gene mutations disrupt synaptic plasticity, memory formation and learning.…”
Section: Mechanisms Of Circadian Plasticity Of the Brainmentioning
confidence: 99%
“…In mammals, the expression of core clock genes has been confirmed not only in the SCN but also in other brain structures, including the cortex and HC (Namihira et al, 1999 ; Reick et al, 2001 ; Shieh, 2003 ; Jilg et al, 2010 ; Ono et al, 2015 ; Riddle et al, 2016 ; Yamaguchi et al, 2016 ). Moreover, several studies have shown that clock gene mutations disrupt synaptic plasticity, memory formation and learning.…”
Section: Mechanisms Of Circadian Plasticity Of the Brainmentioning
confidence: 99%
“…With this approach, the authors were able to record bioluminescence parallel to Per1 activation, which allowed for the quantification of circadian fluctuations directly from the SCN (Yamaguchi et al, ). This technique was then used by many other authors that further improved luciferin delivery, using osmotic pumps (Yamaguchi et al, ). More recently, researchers have also developed double transgenic mice ( Per1–luc and Bmal1–Eluc ), taking advantage of two different types of luc that produce light of different wavelengths (Noguchi et al, ).…”
Section: Evaluation Of Circadian Rhythms: From Cells To Humansmentioning
confidence: 99%
“…and Per2) varies across the 24 hour cycle in the SCN in mice (25,26) and more recently in rats (27). Wang et al, (28) showed that Per2 mRNA and protein expression varied across the 24 hour cycle in the hippocampus.…”
mentioning
confidence: 98%